2010
DOI: 10.1007/s00253-010-2938-z
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of organic compounds solubilized in nonionic surfactant micelles

Abstract: Whether direct availability of organic compound solubilized in nonionic surfactant micelles (bioavailability) in a bioremediation or biotransformation process is uncertain to some extent, which is partially attributed to the difficulty by direct experimental determination. In another point of view, it should be ascribed to the fuzzy concept about the solubilization of organic compound in a nonionic surfactant micelle aqueous solution. In this mini-review, the solubilization of organic compound in surfactant mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Moreover, several studies focused on evaluating the bioavailability of hydrocarbons in surfactant-supplemented samples suggest that compounds entrapped in micelles are not accessible for microorganisms. This fact was mainly proven for non-ionic surfactants (Dai et al 2010; Wang 2011), however recently similar results have been reported for rhamnolipids (Chrzanowski et al 2011; Zeng et al 2011). It is more plausible that the presence of biosurfactants may lead to flushing out potential carbon sources from the vicinity of the cells.…”
Section: Rhamnolipids In Bacterial Cell Motilitymentioning
confidence: 54%
“…Moreover, several studies focused on evaluating the bioavailability of hydrocarbons in surfactant-supplemented samples suggest that compounds entrapped in micelles are not accessible for microorganisms. This fact was mainly proven for non-ionic surfactants (Dai et al 2010; Wang 2011), however recently similar results have been reported for rhamnolipids (Chrzanowski et al 2011; Zeng et al 2011). It is more plausible that the presence of biosurfactants may lead to flushing out potential carbon sources from the vicinity of the cells.…”
Section: Rhamnolipids In Bacterial Cell Motilitymentioning
confidence: 54%
“…1b, 2b2, c2). It has been reported that the nonionic surfactant has two polarities, hydrophilic and hydrophobic (Wang 2011), and that the intracellular hydrophobic pigment could be transported through the cell membrane to the extracellular nonionic surfactant micelles (Hu et al 2012a; Kang et al 2013a). There might be a relationship between pigment solubility in the nonionic surfactant micelles, such as with certain molecules of TX embedded in one pigment molecule.…”
Section: Discussionmentioning
confidence: 99%
“…The solubilization of these moderate polar pigments in nonionic surfactant micelles prevents them from direct contact with microbial cells. The indirect contact between microbial cells and the pigments solubilized in micelles decreases the rate of pigment degradation by the microbial cells (Dai et al ., ; Wang, ). It exhibited as the pigment degradation disappeared with the increase of nonionic surfactant concentration (Fig.…”
Section: Discussionmentioning
confidence: 99%